Measurement of reactive nitrogen loss in lowland rice and associated uncertainties: A Review - Alam, Rounak; Chatterjee, Dibyendu; Parija, Subhra; Pradhan, Abhijit; Swain, Baishali; Das, Brundaban (ORYZA-An International Journal of Rice, 2026)
Nitrogen (N) is a critical macronutrient for rice production, particularly in lowland flooded systems where crop productivity depends heavily on external nitrogen inputs. Global fertilizer-use projections indicate that nitrogen application may reach 130-150 million metric tons annually by 2050, with rice-based systems accounting for a substantial share. In lowland rice, native soil nitrogen is insufficient to meet crop demand, making fertilizer inputs essential for sustaining yields and improving grain nutritional quality. Despite decades of research aimed at enhancing nitrogen use efficiency, effective nitrogen management within the soil-plant-atmosphere continuum remains a major challenge due to inherently high losses of reactive nitrogen under flooded conditions. Processes such as ammonia volatilization, denitrification, and leaching lead to low fertilizer recovery and contribute to environmental and human health impacts, including eutrophication, nitrogen pollution, greenhouse gas emissions, and climate change. This review synthesizes current knowledge on nitrogen loss pathways in lowland rice systems, highlights key methodological challenges and uncertainties in measuring and quantifying reactive nitrogen losses, and examines recent advances in monitoring, modeling, and upscaling approaches. The paper further identifies critical research gaps and discusses implications for mitigation strategies and policy interventions aimed at improving nitrogen use efficiency and promoting the sustainability of lowland rice production.